Single-cell RNA-sequencing reveals cellular heterogeneity and immune microenvironment characteristics between ocular adnexal mucosa-associated lymphoid lymphoma and IgG4−related ophthalmic disease - Yang, Yu; Wang, Yujiao; Jin, Xuelian; He, Weimin (Frontiers in Immunology, 2025)
IntroductionThe molecular pathogenesis of ocular adnexal mucosa-associated lymphoid tissue (MALT) lymphoma and IgG4-related ophthalmic disease (IgG4-ROD) remains incompletely understood. Differentiating between the two diseases is vital given that the diagnostic evaluation and treatment approaches can vary significantly; this difficulty in distinction is exacerbated by the absence of specific biomarkers. This study aimed to investigate the differences between these two diseases based on their cellular composition, transcriptional heterogeneity, and the immune microenvironment using single-cell RNA transcriptional sequencing (scRNA-seq) technology.MethodsWe collected orbital lacrimal gland region tissue samples from three patients with MALT lymphoma and another three with IgG4-ROD and performed single-cell sequencing experiments. Subsequently, we conducted bioinformatics analyses, including cell subpopulation segmentation and inter-group comparison, tumor cell identification, functional enrichment analysis, and pseudotime trajectory analysis. Furthermore, we analyzed the cellular communication between tumor B-cell and T-cell subsets within the immune microenvironment of MALT lymphoma tissues. We performed immunofluorescence assays to verify the co-expression of receptor-ligand pairs.ResultsA total of six major cell subpopulations were identified, with B-cells and T-cells being the predominant cell types. All B-cell subpopulations in MALT lymphomas are malignant, exhibiting significant intratumoral and intertumoral heterogeneity. Reclustering of the T-cell subpopulation identified five major T-cell subpopulations. Pseudotime analysis revealed that CD4+ naive T-cells in MALT lymphoma patients were highly likely to differentiate into follicular helper T-cells, whereas, in IgG4-ROD patients, CD4+ naive T-cells were highly likely to differentiate into regulatory T-cells. Intercellular communication analysis revealed that the CD27-CD70 immune checkpoint receptor−ligand pair and CXCL13-CXCR5 chemokine receptor−ligand pair were significantly upregulated between malignant B-cells and T-cells subpopulations.ConclusionThis study is the first to conduct a comparative single-cell transcriptome sequencing analysis of ocular adnexal MALT lymphoma and IgG4-ROD. Our results reveal the cellular composition, key pathways, and critical immune microenvironment implicated in the development of these two diseases. These findings provide important insights into the pathogenesis of these two diseases and highlight the differences between them.